Skin delivery of epigallocatechin-3-gallate (EGCG) and hyaluronic acid loaded nano-transfersomes for antioxidant and anti-aging effects in UV radiation induced skin damage - Kiran S. Avadhani; Jyothsna Manikkath; Mradul Tiwari; Misra Chandrasekhar; Ashok Godavarthi; Shimoga M. Vidya; Raghu C. Hariharapura; Guruprasad Kalthur; Nayanabhirama Udupa; Srinivas Mutalik (Taylor & Francis Group, 2017)
The present work attempts to develop and statistically optimize transfersomes containing EGCG and hyaluronic acid to synergize the UV radiation-protective ability of both compounds, along with imparting antioxidant and anti-aging effects. Transfersomes were prepared by thin film hydration technique, using soy phosphatidylcholine and sodium cholate, combined with high-pressure homogenization. They were characterized with respect to size, polydispersity index, zeta potential, morphology, entrapment efficiency, Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), X-ray Diffraction (XRD), in vitro antioxidant activity and ex vivo skin permeation studies. Cell viability, lipid peroxidation, intracellular ROS levels and expression of MMPs (2 and 9) were determined in human keratinocyte cell lines (HaCaT). The composition of the transfersomes was statistically optimized by Design of Experiments using Box-Behnken design with four factors at three levels. The optimized transfersome formulation showed vesicle size, polydispersity index and zeta potential of 101.2 ± 6.0 nm, 0.245 ± 0.069 and −44.8 ± 5.24 mV, respectively. FTIR and DSC showed no interaction between EGCG and the selected excipients. XRD results revealed no form conversion of EGCG in its transfersomal form. The optimized transfersomes were found to increase the cell viability and reduce the lipid peroxidation, intracellular ROS and expression of MMPs in HaCaT cells. The optimized transfersomal formulation of EGCG and HA exhibited considerably higher skin permeation and deposition of EGCG than that observed with plain EGCG. The results underline the potential application of the developed transfersomes in sunscreen cream/lotions for improvement of UV radiation-protection along with deriving antioxidant and anti-aging effects.